A via crucis do desejo : a aprendizagem do amor homoerótico nas veredas do Grande Sertão - Santos, Manoel Messias Rodrigues (2009)
When transposing the doorway that leads us to the great labyrinth formed by rosiane paths, we have individuals marked by desire, whose dimensions - sexuality, love, body - are determined by socio-cultural dynamics in which they are inserted. However, if the cultural patterns of sexuality, often reduces the desire to interchangeable forms: the nature desiring almost unlimited in its inventiveness. Therefore, this study aims to examine the settings of homoerotic desire in his connection with the faces of Eros, the novel Grande Sertão: Veredas of João Guimarães Rosa. Thus, there was a sustained theoretical and methodological journey in the tradition of the Sociology of Literature and the hermeneuticphenomenological, since the questioning of homoerotic desire is from the speech of Riobaldo when referred to the image / memory of Diadorim. In this perspective, he is the status in homoerotic tale by performative way, especially with regard to the performance of transvestites Riobaldo / Diadorim and the concept of strangeness which is at the moment Riobaldo be seen by passionate companion. The awareness of that feeling passed between the characters in silences and secrets, wisdom of love that gets them to be, but denied both to be declared. This struggle permeated the whole narrative: on the one hand the feeling of fear and subversive guilt; of another to ensure a love that seems to increase with time. A love that will Riobaldo to rethink their existence, their identity, their being in the world. Diadorim in turn, reveals the ambiguity that reveals the human being. So if the company builds speeches and scripts through which our sexuality is perceived and experienced, and the trajectory of Riobaldo Diadorim shows that, above stereotypes and prejudices, what man is only human.